The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4028/www.scientific.net/amr.1119.647
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and Microstructure Phase of Self Compacting Concrete Using Sea Water as Mixing Water and Curing

Abstract: In Indonesia, several regions have a minimum quantity or none of fresh water. Self Compacting Concrete (SCC) has a dense microstructure. Knowledge about the microstructure and properties of the individual components of concrete have a relationship that is useful for controlling the behavior of concrete. Porosity and microstructure SCC using sea water as mixing water and curing water discussed in this paper. The results showed the higher the compressive strength of SCC sea water is getting smaller porosity. Por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Sea water was collected from Barombong beach, South Sulawesi Province. Table 4 shows mix design of the concrete in 1 m 3 . Freshwater was used for making normal concrete and seawater was used to make sea water concrete.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea water was collected from Barombong beach, South Sulawesi Province. Table 4 shows mix design of the concrete in 1 m 3 . Freshwater was used for making normal concrete and seawater was used to make sea water concrete.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, Portland composite cement has been widely used in concrete construction in Indonesia. Several studies revealed that seawater and Portland composite cement can be used to produce high performance concrete [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by the other studies, this enhancement could be due to the synergistic effects between seawater and SCMs. Microstructural investigations of seawater-mixed SCC have also been performed [62][63][64] and effects of curing methods on strength development in SCC have been explored [61]. Raidyarto et al (2020) demonstrated the feasibility of producing seawater SCC with steel fibers; although corrosion was not explored in this study [66].…”
Section: Self-compacting Concrete (Scc)mentioning
confidence: 96%
“…Researchers in Indonesia [60][61][62][63][64] conducted extensive studies on seawater-mixed SCC using Portland cement (OPC), fly ash, and other materials. Zhou et al [65] developed highvolume fly ash-self compacting concrete with seawater, using large amounts (> 50%) of fly ash replacing cement.…”
Section: Self-compacting Concrete (Scc)mentioning
confidence: 99%